Soil Erosion and Carbon Dynamics. - Roose, Eric J. (Taylor & Francis Group, 2005)
The most complete, nonpartisan source of information on this hot agronomic topic available today, this book brings together a diverse group of papers and data to resolve the debate between sedimentologists and soil scientists and agronomists over whether the effects of soil erosion on carbon and atmospheric CO2 is beneficial or destructive.